Anesthesia Considerations in Patients with Heart Failure who will Undergo Glioblastoma Tumor Removal Surgery - Suranadi, I Wayan; Adistaya, Anak Agung Gde Agung; Jeanne, Bianca (Jurnal Neuroanestesi Indonesia, 2025)
Perioperative complications in neurosurgery encompass a range of issues, including hemodynamic instability, significant bleeding, extended procedure durations, and unusual patient positioning. Additionally, fluctuations in carbon dioxide levels, whether hypercapnia or hypocapnia, can contribute to secondary brain injury. Hemodynamic instability is particularly likely during critical moments such as laryngoscopy and intubation, head pins, and the manipulation of the scalp, bone, and dura mater. Patients with congestive heart failure (CHF) and other cardiovascular comorbidities require special attention throughout the entire surgical process, from the preoperative period through to postoperative care. Here, we present a case study on the successful anesthesia management of a patient with moderate heart failure undergoing glioblastoma tumor removal surgery. This case underscores the necessity of individualized anesthetic approaches and vigilant monitoring to minimize risks and ensure patient safety in complex neurosurgical procedures. The main goal of anesthesia in CHF patient undergo neurosurgical procedure are to maintain cerebral perfusion pressure, decrease Intracranial Pressure, Cardiovascular monitoring, maintain hemodynamic stability using vasopressor, inotrope, and fluid balance, and special consideration of position and long surgical time. By carefully managing these perioperative challenges, we can improve outcomes for patients with significant comorbidities undergoing high-risk surgeries.